Case Report: Laki-Laki Usia 42 Tahun dengan Laryngopharingeal Refluks - Farhan Ridho Pangestu; Mukhlis Imanto (CV. Jasa Sukses Abadi, 2026)
Laryngopharyngeal Reflux (LPR) is an inflammatory condition affecting the mucosa of the larynx and pharynx caused by the retrograde flow of gastroduodenal contents into the upper aerodigestive tract. This condition is frequently underdiagnosed due to its nonspecific symptoms, which often mimic other upper airway disorders. LPR presents with a wide range of clinical manifestations and is commonly managed by multiple medical disciplines without an accurate or standardized diagnostic approach. This case report aims to describe the clinical presentation, risk factors, diagnostic process, and management of LPR in an adult patient. We report the case of a 42-year-old male who presented with recurrent choking sensations, shortness of breath, dry cough, frequent throat clearing, and hoarseness persisting for four months, accompanied by worsening heartburn and epigastric discomfort. The patient had several predisposing factors, including obesity and unhealthy lifestyle habits such as high-fat and acidic food consumption and lying down shortly after meals. The diagnosis of LPR was established based on a Reflux Symptom Index (RSI) score of 14 obtained during anamnesis and a Reflux Finding Score (RFS) of 9 derived from indirect laryngoscopic examination. Management consisted of pharmacological therapy with high-dose proton pump inhibitors and antacids, combined with non-pharmacological interventions including lifestyle and dietary modifications. This integrated approach aims to reduce reflux episodes and mucosal inflammation. This case highlights the clinical importance of RSI and RFS as practical diagnostic tools for LPR and emphasizes the need for comprehensive management strategies to improve patient outcomes and quality of life.